JUDGE'S CONSIDERATIONS IN RESOLVING EXECUTION PARATE DISPUTES (CASE STUDY OF MA DECISION NUMBER 2553 K/Pdt/2016) - Rahmadhani, Nining (IBLAM LAW REVIEW, 2024)
This research aims to examine the judge's considerations in resolving disputes regarding the execution of Supreme Court Decision Number 2553 k/pdt/2016. The research method uses a qualitative approach with a normative juridical research type and library data collection techniques regarding legal sources related to this research, then concluded with deductive analysis. The research results show that the source of law in the judge's consideration refers to statutory regulations, namely Article 6 UUHT which states that executions are carried out without the fiat of the Chief Justice. The decision also took into account the facts presented at the trial and decided that one of the parties had committed an act of breach of contract or breach of contract and that the actions taken by the creditor did not constitute an unlawful act. However, the judge's considerations in this decision did not refer to the general explanation of number 9 UUHT which explains that the execution of mortgage rights is based on the fiat of the Chief Justice. So that the implementation of the UUHT execution still contains confusion and vague diction which results in legal uncertainty.